Carbon nanotubes growth from camphoric carbon sources using transition metal catalysts / Azira Abd Aziz - Abd Aziz, Azira (Institute of Graduate Studies, UiTM, 2012)
This thesis covers the analysis of catalytic growth of carbon nanotubes (CNTs) under well-defined conditions, the optimization of the catalyst and introduces model for the growth mechanism based on the experimental results. Experimental investigations are presented to obtain a comprehensive picture on the catalytic growth of CNTs. The overall aim of this thesis is to deposit CNTs by the seeded catalyst method and the modified fluidized floating catalyst method by Chemical Vapour Deposition (CVD) and to investigate the effects of starting material and catalysts on the morphology and structure of the deposited CNTs. Camphor (C10H16O, crystalline state) and camphor oil (liquid state) are the precursor materials used as the source of CNTs. Transition metal (Fe, Ni, Co, Mn, Al, Mg) catalysts were prepared and the effect on their catalytic behavior were studied. Metal catalysts have been prepared by sol-gel method with or without support catalyst. Correlation between the catalyst particle size and CNT diameter has been the motivation to reduce the catalyst particle size down to nanoparticle size.